The Influence of Transformational Leadership Style, Job Satisfaction and Organizational Culture on Turnover Intention in Employees of PT. Medan Distribusindo Raya Kabanjahe - Rommel Sitohang (Asian Journal of Management Analytics, 2023)
The purpose of this study was to determine and analyze the influence of transformational leadership style, job satisfaction, and organizational culture on the turnover intention of employees of PT. Medan Distribusindo Raya Kabanjahe. The results of this study indicate that transformational leadership style, job satisfaction, and organizational culture have a significant influence on turnover intention. This is indicated by the Fcount (7.752) > Ftable 2.72 with Sig-p (0.000) < (0.05). The transformational leadership style partially has a positive and significant influence on turnover intentions. This is indicated by the values of tcount (2.061) > ttable (1.991) and Sig (0.029) < (0.05). Job satisfaction partially has a positive and significant effect on turnover intention. This is indicated by the values of tcount (3.908) > ttable (1.991) and Sig (0.000) < (0.05). Organizational culture partially has a positive and significant influence on turnover intentions. This is indicated by the values of tcount (2.111) > ttable (1.991) and Sig (0.038) < (0.05). Transformational leadership style, job satisfaction, and organizational culture have an influence on turnover intentions of 44.2%.